Blunt duodenal injury in a 9-year-old boy: A case report - Muhammad Arif Mateen Khan; Syed Waqas Ali; Zaeem Ur Rehman Khan; Yaqoot Jahan (Journal of Pediatric Surgery Case Reports)
Introduction: Blunt abdominal trauma leading to isolated duodenal injury is rare in children. Duodenal injuries are often accompanied by damage to adjacent organs, making their diagnosis challenging. Case study: A 9-year-old boy presented with severe abdominal pain following a blunt handlebar injury the day before. He was tachycardic and tachypneic and had generalized abdominal guarding and tenderness. Computerized tomography (CT) imaging showed retroperitoneal air around the right kidney, suspicious for a duodenal injury. He underwent an exploratory laparotomy during which we identified a 2 × 2 cm perforation in the second portion of the duodenum. We repaired it primarily using interrupted 3-0 braided reabsorbable sutures in a single layer and covered the sutures with an omental patch. We also did a gastrostomy, a tube duodenostomy, and a jejunostomy. Jejunostomy feedings were initiated on postoperative day 5. Two days later, he developed severe abdominal pain and abdominal distension. Plain films suggested an intestinal obstruction. He underwent an exploratory laparotomy during which we found and took down adhesions between bowel loops and the duodenal repair site. The duodenostomy and the jejunostomy were closed at that time, and a drain was placed next to the duodenal repair site. Two days later bilious fluid was seen in the drain, indicating a duodenal leak. The patient was managed conservatively with octreotide and total parenteral nutrition (TPN). The leak resolved spontaneously by postoperative day 13, confirmed via contrast study. As oral intake was gradually reintroduced, he developed recurrent abdominal pain, distension, and bilious gastrostomy output, suggestive of another intestinal obstruction. He underwent a third exploration with lysis of adhesions. An iatrogenic jejunal perforation occurred, which was managed by a jejunostomy. He was managed with a high-protein diet. Three months after the initial intervention, the jejunostomy was taken down, and he was successfully discharged home shortly after. Conclusion: While primary repair is the preferred treatment for duodenal perforations, delayed presentations may necessitate alternative approaches such as duodenal diverticulization or duodenal bypass with temporary or permanent pyloric exclusion.